Pengembangan Panduan Bimbingan Klasikal Teknik Sinema Edukasi untuk Meningkatkan Resiliensi Siswa SMKN 2 Malang - Yuniar Fitri Ahfadzi; Khairul Bariyyah; Laily Tiarani Soejanto (Indonesian Counselor Association (IKI), 2023)
Resilience is the capacity of an individual to rise, confront, and surmount problems or situations that deviate from their plans. Resilience is the strength or endurance of a person to face, overcome, and become stronger when encountering problems. One method to enhance student resilience is educational cinema. The purpose of this developmental research was to create a product in the form of a guide for school counselors that can assist in improving student resilience. This guide is intended to be acceptable and meet the standard evaluation criteria of utility, feasibility, appropriateness, suitability, and attractiveness, and to produce an effective student resilience enhancement counseling model using the educational cinema method. The outcome of this research is a student resilience enhancement counseling model utilizing educational cinema techniques. This model has undergone a material expert evaluation phase, receiving a total score of 128 with an average of 3.76 and a percentage of 94%. This indicates that the product is highly valid and very suitable for use. The product design expert evaluation yielded a total score of 96.5, with an average of 3.86 and a percentage of 96%, suggesting that the product is highly valid and very suitable for use. Finally, the assessment from potential product users (Counselors) resulted in a total score of 117 with an average of 3.9 and a percentage of 97%, signifying that the product is highly valid and very suitable for use